Management of epilepsy in pregnancy: a report from the International League Against Epilepsy Task Force on Women and Pregnancy - Torbjörn Tomson; Dina Battino; Rebecca Bromley; Silvia Kochen; Kimford J. Meador; Page B. Pennell; Sanjeev V. Thomas (2019)
ABSTRACT The risks associated with use of antiepileptic drugs during pregnancy are a major concern for all women with epilepsy with childbearing potential. These risks have to be balanced against foetal and maternal risks associated with uncontrolled seizures. This report from the International League Against Epilepsy Task Force on Women and Pregnancy aims to provide a summary of relevant data on these risks as a basis for expert opinion recommendations for the management of epilepsy in pregnancy. The report reviews data on maternal and foetal risks associated with seizures as well as teratogenic risks associated with antiepileptic drug exposure, including effects on intrauterine growth, major congenital malformations, and developmental and behavioural outcomes. The impact of pregnancy on seizure control and on the pharmacokinetics of antiepileptic drugs are also discussed. This information is used to discuss how treatment may be optimized before conception and further managed during pregnancy.